2017
DOI: 10.4172/pharmaceutical-sciences.1000301
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Chronic Pain Treatment with Opioids

Abstract: Pain is an unpleasant sensation that can range from mild, localized discomfort to agony. The International Association for the Study of Pain's widely used definition states, "pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage" [1][2] . Pain mechanism is a complex phenomenon in which pain is induced by numerous pain modulating systems [2] , sensitized by the neurophysiological systems. Pain can be influenced by the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Furthermore, studies are also required to explore the relevant mechanism. For patients at an early stage of AP, the severity and importance of organs involved in the injuries are more than the pancreas itself (Liu et al, 2006, Dos Santos et al, 2018, Alsharidah et al, 2018, Yildiz et al, 2017, Pati et al, 2017, Tatar et al, 2017), while multi-organ injuries are strongly associated with the inflammatory responses caused by hyperglycemia. Thus, in clinical treatment of AP, great attention should be paid to the glucose level, and rational control of glucose might be critical to the development and treatment of AP through affecting the inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies are also required to explore the relevant mechanism. For patients at an early stage of AP, the severity and importance of organs involved in the injuries are more than the pancreas itself (Liu et al, 2006, Dos Santos et al, 2018, Alsharidah et al, 2018, Yildiz et al, 2017, Pati et al, 2017, Tatar et al, 2017), while multi-organ injuries are strongly associated with the inflammatory responses caused by hyperglycemia. Thus, in clinical treatment of AP, great attention should be paid to the glucose level, and rational control of glucose might be critical to the development and treatment of AP through affecting the inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is immune activation in patients with depression. Thymus and spleen are two important immune organs in the body (Wan et al, 2017, Tong, 2014, Naveed et al, 2018, Babenko et al, 2017, Pati et al, 2017, Tatar et al, 2017, Peng et al, 2017, Gao et al, 2017). The pathological changes of spleen and thymus in chronic stress depression rats can be improved significantly after intervention, indicating that it can alleviate the pathological development of depression by interfering with the immune system.…”
Section: Discussmentioning
confidence: 99%
“…El dolor crónico -como enfermedad-representa -al mismo tiempo-uno de los problemas médicos, jurídicos y sociales (14,23,56,57) más preocupantes y silenciosos para la sociedad del siglo XXI. A lo largo de los últimos años, la reflexión e investigación se ha priorizado en este sentido, generándose mayor conciencia en cuanto al sufrimiento relacionado con la salud (19,58).…”
Section: Discussionunclassified